Assessment of antioxidant potential in seed extracts of Nyctanthes arbor-tristis L. and phytochemical profiling by Gas Chromatography-Mass Spectrometry system - Awadhesh Kumar Mishra; Kavindra Nath Tiwari; Rajesh Saini; Jitendra Kumar Chaurasia; Sunil Kumar Mishra (Universidade de São Paulo, 2023)
Abstract The present study has been carried out with the seed extracts of Nyctanthes arbor-tristis L. (Parijat) and evaluates its antioxidant potential and profiling the phytochemical constituents by Gas Chromatography-Mass Spectrometry (GC-MS) analysis. The antioxidant potential of the seed extracts was measured by four different in vitro assay like 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity, superoxide anion free radical scavenging activity, ferric reducing antioxidant power (FRAP) and lipid peroxidation inhibition potential (LPIP) assay. The total phenol content (TPC) and total flavonoid content (TFC) were estimated. The ethyl acetate extract (EAE) of seeds showed potential DPPH free radical scavenging activity (EC50 129.49±3.55µg/ml), superoxide anion radical (EC50 969.94±8.03µg/ml) and LPIP (EC50 452.43±5.07 µg/ml) activities. The total phenol content was maximum in aqueous extract (AQE) which was 201.00±0.20 µg/mg gallic acid equivalent. The EAE was rich with total flavonoid and it was found to be 34.50±0.40 µg/mg rutin equivalent. The EAE was subjected for phytochemical-profiling using GC-MS system. The presence of different phytoconstituents supports the medicinal value of the seeds. The results suggest that EAE constitutes a promising new source of novel compounds. Further, it can be used for isolation and purification of specific compounds which have good antioxidant activities and possess useful biological activities.